REFLECTION OF THEONYMIC FEATURES IN ANTHROPONYMS - Qobilov Mirziyo Eshnozar ogli (Scholar Express Journal, 2025)
This article is devoted to the study of theonymic anthroponyms, that is, personal names derived from religious sources. The article studies in detail the etymological, semantic and linguistic aspects of theonymic anthroponyms. The author analyzes the features of the use of theonymic anthroponyms in different cultures and reveals their linguocultural significance. The study covers the principles of formation, classification and place of theonymic anthroponyms in the modern language system. The article presents, along with the theoretical foundations of this topic, practical examples. As a result of the study, the linguistic identification of theonymic anthroponyms and the features of their use in a socio-cultural context were determined
Keywords: theonym; theonymic anthroponym; onomastics; toponymy